What is driving Taiwan government for policy change in higher education after the year of 2016 – in search of egalitarianism or pursuit of academic excellence?. Issue 2 (1st February 2022) - Hou, Angela Yung Chi; Hill, Christopher; Hu, Zoe; Lin, Lily
ABSTRACT: Due to global influence and local demand, Taiwan's higher education system has experienced great changes in policy agenda and system reform over the past few decades. After President Tsai took the presidential office in 2016, the Ministry of Education (MOE) shifted its focus towards universities' autonomy and social responsibility, which encouraged institutions to strengthen their partnerships and collaborations with other ASEAN countries. Based on this new ideological and political paradigm shift, three key national higher education projects, including the new cycle of self-accreditation policy, higher education sprout project, and new southbound policy, were implemented. Therefore, the aim of this paper is to present the current development of these three MOE initiatives since 2016, and analyze the paradigm shift of Taiwan higher education policymaking in terms of egalitarianism. Four major findings are addressed as follows. First, policy and politics mattered in the process of educational policy shift under a doctrine of egalitarianism; second, national accreditation continued to be used by university leaders for institutional effectiveness; third, global competitiveness in Taiwan higher education is declining gradually; fourth, the loss of Chinese students was not offset by the new Southbound program.